Profile defining variables of immigrant university student - Gloria Pérez Serrano; Mª Luisa Sarrate Capdevila (Universidad de La Rioja, 2013)
Cultural diversity is a defining characteristic of current society. Migrations have in recent years become a timeless constant, a constant that requires a search for mechanisms that can cope with this new reality without triggering rifts or confrontations. It may be asserted that the meeting of different cultures in the same geographic space is today a structural fact. International organizations are committed to promoting living together in pluricultural realities and fighting for the acknowledgement of minority rights. The university, as an institution of higher education, has as its mission the training of highly qualified professionals, and this mission must be made to extend to the foreign population. The objective of this paper is to define the profile of the immigrant university student in order to identify his or her differential traits. A quantitative and qualitative methodology has been used. A Likert-scale questionnaire and a semi-structured interview were applied. The data were analyzed using different computer packages. Foremost among the main results is the fact that the population at issue chooses to attend university in order to continue their education, improve their job situation and legalize their certificates of educational accomplishment. They prefer long-term studies in order to have more opportunities in a competitive job market. Their expectations are high, aimed at improving their quality of life. The paper concludes with the contribution of positive discrimination measures to favour the social inclusion of this population.